Let AB = x
Let r be the radius of the semi circle.
It implies;
OC = x-r
y = √(r²-(x-r)²)
y = √(r²-(x²-2xr+r²))
y = √(2xr-x²)
Therefore;
6²+r² = (x-r)²+(2+√(2xr-x²))²
6²+r² = x²-2xr+r²+4+4√(2xr-x²)+2xr-x²
6²+r² = r²+4+4√(2xr-x²)
32 = 4√(2xr-x²)
8 = √(2xr-x²)
64 = 2xr-x²
64+x² = 2xr
r = (64+x²)/(2x) -------- (1)
z = √((x+r)²-r²)
z = √(x²+2xr+r²-r²)
z = √(x²+2xr)
It implies;
(√(x²+2xr)+6)² = (2x)²+(2+√(2xr-x²))²
x²+2xr+12√(x²+2xr)+36 = 4x²+4+4√(2xr-x²)+2xr-x²
2x²+12√(x²+2xr)+32 = 4x²+4√(2xr-x²)
12√(x²+2xr)+32 = 2x²+4√(2xr-x²)
Dividing through by 2.
6√(x²+2xr)+16 = x²+2√(2xr-x²) ------ (2)
Calculating x.
Substituting (1) in (2).
6√(x²+2x((64+x²)/(2x))+16 = x²+2√(2x((64+x²)/(2x))-x²)
6√(x²+64+x²)+16 = x²+2√(64+x²-x²)
6√(2x²+64)+16 = x²+16
6√(2x²+64) = x²
36(2x²+64) = x⁴
x⁴-72x²-2304 = 0
Let x² = t
Therefore;
t²-72t-2304 = 0
It implies;
t ≠ -24
t = 96
And x² = t
Therefore;
x² = 96
x = √(96)
x = √(16*6)
x = 4√(6) units.
And x = AB = BC.
Therefore;
AB = BC = 4√(6) units.
At (1).
r = (64+x²)/(2x)
Substituting the value of x = AB = BC in (1) to get r.
r = (64+(4√(6))²)/(2(4√(6)))
r = (64+96)/(8√(6))
r = 160/(8√(6))
r = 20/√(6)
r = ⅓(10√(6)) units.
The required angle theta is;
Let it be a.
sina = (r/(x+r))
sina = ⅓(10√(6))/(⅓(10√(6))+4√(6))
sina = (⅓(10√(6)))/(⅓(22√(6)))
sina = (10/22)
sina = 5/11
a = asin(5/11)°
a = 27.03569178941°
Or
The base of the right-angled triangle is;
AC = 2(AB)
AC = 8√(6) units.
The height of the right-angled triangle is;
2+y
y = √(2xr-r²)
And x = 4√(6), r = ⅓(10√(6)).
height = 2+√(2*4√(6)*⅓(10√(6))-(4√(6))²)
= 2+√(160-96)
= 2+√(64)
= 10 units.
Therefore the required angle theta is;
Let it be a.
tana = 10/(8√(6))
tana = 5√(6)/24
a = atan(5√(6)/24)
a = 27.03569178941°
We appreciate you contacting us. Our support will get back in touch with you soon!
Have a great day!
Please note that your query will be processed only if we find it relevant. Rest all requests will be ignored. If you need help with the website, please login to your dashboard and connect to support